Exposure of the physical state of the home environment to the incidence of ARI in the Sangaji Village coastal area - Sakriani,; Supardi, Ummi Kalsum (International Journal of Scientific Research and Management (IJSRM), 2023)
Nearly all health centers list ARI among the top 10 ailments each year. ARI may be a contributing factor in death in specific age groups. The physical environment of the home, in particular, can have an impact on the development of ARI disease. Determining the physical environment of the home's exposure to the occurrence of ARI is the goal of this study. This study uses a case-control study design and is observational in nature. implemented at Ternate City's Sangaji Village's coastal area. There were 76 respondents in the study's sample. To ascertain how exposed the physical environment of the home was to ARI episodes, information was gathered using measurements, interviews, and observations. To ascertain the relationship between the variables under study, apply the Chi-square test. The study's findings demonstrated that there was no correlation between the incidence of ARI and illumination (p-value = 1.000), floor (p-value = 0.381), or humidity (0.185). Conversely, there is a statistically significant correlation (p-value=0.037) between ventilation and the incidence of ARI. In summary, the majority of the respondents' home condition factors do not fit the criteria. The ventilation variable was linked to the incidence of ARI among the five physical condition factors of the residence under study. It is therefore advised that this study looks at aspects related to home conditions and how they affect other health issues, particularly conditions that are based on the physical state of the home. This study demonstrates a strong correlation between home ventilation and ARI incidence. Other factors including humidity, floor, and temperature, however, did not demonstrate a meaningful correlation. Thus, other aspects of living environments that may have an impact on health can be the subject of future research.